Analysis of the content of the computer book for the fifth grade preparatory in the light of the thinking skills of the axial (Journal of the College of Basic Education, 2022)
The research aims to analyze the fifth grade computer book according to the axial thinking skills. The number of pages analyzed (108), and the results revealed that the inclusion of skills in the book was random for those skills, and the researcher realized not to rely on a specific criterion by type of skill. There is also a clear weakness and disparity in rates in the content of the methodological book.